Modelling of water demand and supply to develop future management scenarios for Mokolo River Catchment, Limpopo Province - Nkoe, E. B. (My University, 2025)
Effective planning and integrated management of water resources in a rapidly changing environment under the influence of climate change and anthropogenic activities relies on consistent monitoring of changes in a river basin from these diverse impacts. The identification of the root causes of changes in river basins will inform the development and use of appropriate interventions. In the Mokolo River Basin of Limpopo, a comprehensive modelling study was conducted to evaluate water demand and supply dynamics using the Water Evaluation and Planning (WEAP) framework. This study involved manual calibration of the catchment, yielding calibration results characterised by a coefficient of determination (R²) of 0.80 and a Nash-Sutcliffe Efficiency (NSE) of 0.55, alongside validation results of R² = 0.70 and NSE = 0.61. These metrics indicate a fair level of model performance, suggesting that the WEAP model can effectively simulate the hydrological processes within the basin. The analysis revealed that water demand was adequately met for the baseline year of 2010, indicating a stable supply-demand equilibrium during this period. However, projections for the future, specifically from 2025 to 2045, indicate a significant challenge in meeting water demand, particularly within the mining and industrial sectors. This anticipated unmet demand highlights the pressing need for strategic water management interventions in the basin. Five management scenarios were therefore implemented to address these issues, focusing on reducing water use across irrigation, domestic, and industrial sectors, while also considering inter-basin water transfers as a viable solution. The results of these scenarios demonstrated that implementing such measures could substantially alleviate unmet demand, accentuating the importance of integrated water resource management strategies in the face of increasing water scarcity.
Thesis (M.Sc.(Geography and Environmental Science)) -- University of Limpopo, 2025
Keywords: Modelling Water demand and supply; Future management scenarios; Mokolo River; Limpopo province; WEAP model; Water -- Distribution; Water-supply -- South Africa -- Limpopo; Water-supply; Watersheds